Estrus induction in the non-breeding season is not associated with hydrometra in dairy goats (Research, Society and Development, 2021)
This study aimed to compare the prevalence of hydrometra (HD) at the end of the reproductive season in goats subjected (HORM and LIGHT) or not (Control-HORM and Control-LIGHT) to estrus induction by either hormonal protocol or light program, respectively, in the non-breeding season. HORM-goats received intravaginal sponges (six days) associated with cloprostenol plus eCG 24 h before sponge removal while LIGHT-goats were submitted to 16 h of light and 8 h of darkness for 60 days. Pregnant goats from both groups gave birth at the early reproductive season and were evaluated by transrectal ultrasound ~45 days after the end of the season. The control goats (Control-HORM and Control-LIGHT) were also examined. There was no difference in the prevalence of HD between goats from HORM (8/31; 25.8%) compared to Control-HORM (4/26; 15.4%), or LIGHT (9/54; 16.7%) compared to Control-LIGHT (7/51; 13.7%), as well as between HORM and LIGHT groups. In conclusion, estrus induction with both hormonal and light protocols is not associated with the development of HD in dairy goats.